Oltre i muri: il caso di Bidisha (Altre Modernità, 2021)
A director, a successful journalist (working for The Daily Telegraph and TheIndependent), the author of two best-selling novels which consecrated her fame as anartist (Seahorses, 1997, and Too Fast to Live, published three years later), for the past tenyears, Bidisha has devoted her talent to creating narratives that mix fictional and nonfictionalelements (namely testimonies and reports). After Venetian Masters (2008), anautobiographical work where she revealed the cultural biases behind the seemingly impeccable façade of Venetian society, Bidisha seemingly started a project aimed at theinclusion of those who are commonly marginalized. Indeed, she is engaged inmetaphorically dismantling walls, which may be either real and tangible, or invisible,such as those that prevent the refugees in London from being properly acknowledged.By focusing on Beyond the Wall: Writing a Path through Palestine (2012) and Asylum andExile: The Hidden Voices of London (2014), this essay sets out to investigate the strategiesemployed by the writer to document what walls normally hide, thus restoring thedignity of precarious lives, striving to resist cultural annihilation.
Keywords: Asylm and Exile; Beyond the Wall; Bidisha; Walls; Refugees